(untitled) (Altre Modernità, 2025)
This article aims to provide a deeper understanding of the dynamics of success in the Italian digital literary sphere through an analysis of BookTok, a community that remains largely unexplored in academic research. After emphasizing the need to examine online dynamics to grasp literary success, the study introduces the BookTok community and its mechanisms. In particular, the act of book recommendation is framed within the context of cultural intermediation, highlighting the central role of emotional response. Special attention is given to videos in which readers film themselves crying while reading a book – an expression of emotional performativity that takes on a collective dimension. Recognizing the social value of emotions, the article proposes viewing BookTok as an emotional community that attributes value to shared affective experiences. Through an analysis of selected videos and comments, the study explores the concept of literary value and the ways in which it is constructed within these participatory communities. In the final section, a brief analysis of A Little Life is presented, situating it within broader trends in contemporary literature.